Learning Management System in Madrasah: A Study of Teacher Readiness and Acceptance of Technology - Hidayati, Dian; Rifa’i, Andi Arif; Rochmah, Shofia Noor Wachidatur (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to analyze the application of learning management systems in the form of technology to support the implementation of learning. Specifically, this study aims to ascertain the relationship between the teacher's technology acceptance model and the technology readiness index. At the elementary school (SD/MI), junior high school (MTs), senior high school (MA), and vocational schools in the city of Bandung, 185 private teachers participated in the survey. The results showed that perceived ease of technology was positively and significantly influenced by optimism and innovation, positively and significantly influenced by insecurity, and negatively or not significantly affected by discomfort. Then, optimism significantly increases people's perception of how helpful technology can be. While innovativeness and inconvenience have little effect on how useful technology is for people, perceived ease of use and insecurity have a small but positive effect. The implications of this research can be explained by the fact that teachers' acceptance of technology in learning can determine their optimism and innovation in learning. Therefore, teachers must be encouraged to prepare various skills and competencies to use technology to support their teaching and learning activities.